Pre-operative dysglycemia is associated with decreased survival in patients with pancreatic neuroendocrine neoplasms - Sandini, Marta; Strobel, Oliver; Hank, Thomas; Lewosinska, Magdalena; Nießen, Anna; Hackert, Thilo; Büchler, Markus W.; Schimmack, Simon (Surgery, 2020)
Diabetes mellitus is associated with increased risk of pancreatic cancer and impaired postresection survival. For pancreatic neuroendocrine neoplasms,…